2019
DOI: 10.3168/jds.2019-17265
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Production performance and nutrient digestibility of lactating dairy cows fed diets with and without addition of a live-yeast supplement

Abstract: The objective of this study was to evaluate the use of a live-yeast product when feeding relatively high-forage diets to high-producing cows in mid lactation. Eight primiparous [607 ± 43 kg of body weight (BW) and 130 ± 16 d in milk (DIM) at the beginning of the experiment] and 16 multiparous (706 ± 63 kg of BW and 137 ± 22 DIM at the beginning of the experiment) Holstein cows were blocked by parity and DIM, and randomly assigned to 1 of 2 diets (control vs. yeast) for a 12wk period according to a randomized c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…(2020) added yeast to the diets of ewes and reported an increased milk yield, improved milk fat, increased milk protein, and solids rather than fats. Contrary to the above studies, some authors reported no effect of yeast treatment on milk yield and milk fat in lactating Holstein cows ( Ambriz-Vilchis et al., 2017 ; Al- Mallah, 2018 ; Ferreira, 2019 ). Similarly, the milk yield, milk fat, and milk protein of buffalo cows were not affected by yeast supplementation ( Ramírez et al., 2007 ).…”
Section: Growth Performance and Quality Of Ruminant Products Following Yeast Treatmentmentioning
confidence: 64%
See 1 more Smart Citation
“…(2020) added yeast to the diets of ewes and reported an increased milk yield, improved milk fat, increased milk protein, and solids rather than fats. Contrary to the above studies, some authors reported no effect of yeast treatment on milk yield and milk fat in lactating Holstein cows ( Ambriz-Vilchis et al., 2017 ; Al- Mallah, 2018 ; Ferreira, 2019 ). Similarly, the milk yield, milk fat, and milk protein of buffalo cows were not affected by yeast supplementation ( Ramírez et al., 2007 ).…”
Section: Growth Performance and Quality Of Ruminant Products Following Yeast Treatmentmentioning
confidence: 64%
“…(2007) Holstein Friesian cows Mid-lactation Concentrate 2.5 g yeast/cow per day Increased milk yield; no effects on milk composition Maamouri et al. (2014) Holstein cows 20 ± 2 wk of lactation Forage and concentrate 10 g yeast/cow per day Increased milk yield; increased yield of milk fat Rezaeian (2003) Holstein cows 130 ± 16 DIM Forage and concentrate 5.4 × 10 11 CFU yeast per day No effects on milk fat yield, milk yield, milk protein concentration; no effects on milk protein yield, milk lactose concentration, and milk lactose yield Ferreira (2019) Holstein cows 21 d prepartum to 60 d postpartum Forage and concentrate 4 g yeast/cow per day Increased milk total solid; increased concentrations of milk fat; increased milk yield Nasiri et al. (2019) Holstein cows 95 ± 12 DIM Forage and concentrate 35 g yeast/cow per day No effects on milk yield, fat corrected milk, milk fat; no effects on milk protein and lactose Al- Mallah (2018) Holstein cows 176 ± 18 DIM Forage and concentrate 15 g inactivated dry yeast/cow per day Increased milk yield; increased milk fat; increased lactose concentration Dias et al.…”
Section: Growth Performance and Quality Of Ruminant Products Following Yeast Treatmentmentioning
confidence: 99%